Produktivitas Karyawan UMKM: Tinjauan dari Perspektif Motivasi dan Lingkungan Kerja - Alfa Ridho, Syeikhu; Adriyan, Fahmi; Rahma Windayati, Della; Alfiana Abdilla, Nirma (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Human resources play a strategic role in supporting the success of SMEs. In mushroom-based SMEs, employee productivity is influenced by multiple internal factors, especially motivation and work environment. This study highlights the strategic importance of optimizing these factors to improve productivity in mushroom cultivation SMEs in Malang Regency. This research is to Analyzing the influence of motivation and work environment in improving employee productivity at Restu Bunda Mushroom Cultivation SME. This study uses a quantitative method with a saturated sampling technique involving 57 employees. Data were collected via questionnaires and analyzed using multiple linear regression, classical assumption tests, and coefficient of determination analysis. The results indicate that both work motivation and the work environment significantly influence employee productivity.